The Existence of Financial Independence Management in Modern Islamic Boarding Schools (Case Study of the Role of Charity Business in Supporting the Operations of Al Basyariyah Islamic Boarding School) - H. Soro , Suharyanto; Sanjaya, Dinar (Global Education Journal, 2025)
Islamic boarding schools as Islamic educational institutions face major challenges in maintaining financial operational sustainability amidst dynamic social and economic changes. This study aims to analyze the management of financial independence at Al Basyariyah Islamic Boarding School with a focus on the role of charitable efforts in supporting the operational activities of the Islamic boarding school. The approach used in this study is a case study. Data collection was carried out through participant observation, in-depth interviews, and documentation. The results of the study indicate that the management of financial independence at Al Basyariyah Islamic Boarding School is carried out through six main stages: planning, organizing, implementing, controlling, identifying constraints, and compiling solutions. Each stage shows a structured process based on Islamic values and modern management principles. Important findings include the existence of a diversification system of business units that generate stable income, such as the production of bottled water, confectionery, bakery, and cooperatives. However, Islamic boarding schools also face challenges such as a lack of professional staff in the managerial field, limited market access, and challenges in human resource regeneration. This study concludes that institutional strengthening, sharia-based entrepreneurship training, and collaboration with alumni and the surrounding community are effective strategies in overcoming these obstacles.